Cross-linguistic Influence Among Dutch-English Bilinguals’ Associations to False Cognates - Huttenga, Gezina (Student Undergraduate Research E-journal!, 2015)
Research among 39 Dutch students of English shows influence of both their languages on each other when performing a word association task involving false cognates. For the task, twelve words were selected that showed both orthographic and phonemic similarity in English and Dutch, but differed in meaning. When performing the experiment in either an exclusively English or Dutch setting, bilingual respondents’ associations to these words showed influence from the non-experiment (or “other”) language. The same experiment was also conducted among two control groups. While the English controls (n=27) showed no or negligible evidence of Dutch influence on their English, the Dutch controls (n=37), who were also exposed to English on a daily basis, also showed substantial evidence of English in their associations.